Comparing Tobacco and Alcohol Policies From a Health Systems Perspective: The Cases of the Philippines and Singapore - Gianna Gayle Herrera Amul; Gianna Gayle Herrera Amul; Gianna Gayle Herrera Amul; Jean-Francois Etter (Frontiers Media S.A., 2022)
Objective: To provide a comparative analysis of current tobacco and alcohol control laws and policies in the Philippines and SingaporeMethods: We used a public health law framework that incorporates a systems approach using a scorecard to assess the progress of the Philippines and Singapore in tobacco and alcohol control according to SDG indicators, the WHO Framework Convention on Tobacco Control and the WHO Global Strategy to Reduce Harmful Use of Alcohol. We collected data from the scientific literature and government documents.Results: Despite health system differences, both the Philippines (73.5) and Singapore (86.5) scored high for tobacco control, but both countries received weak and moderate scores for alcohol control: the Philippines (34) and Singapore (52.5). Both countries have policy avenues to reinforce restrictions on marketing and corporate social responsibility programs, protect policies from the influence of the industry, and reinforce tobacco cessation and preventive measures against alcohol harms.Conclusion: Using a health system-based scorecard for policy surveillance in alcohol and tobacco control helped set policy benchmarks, showed the gaps and opportunities in these two countries, and identified avenues for strengthening current policies.